2004
DOI: 10.1023/b:plan.0000036375.40006.d3
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Regulates Elongation of Carrot Somatic Embryo Radicles as a Signal Molecule

Abstract: Elongation of carrot somatic embryo radicles was inhibited by sucrose at or above 5% (145 mM). This effect would not be released until the sucrose concentration was lowered again. Morphological and cytological studies as well as determination of ABA content and analysis of the expression mode of a Lea gene, all point to its similarity to natural dormancy and germination of seeds. Use of monosaccharides (glucose and fructose), other disaccharide (maltose), and isomolar concentration of osmotica (mannitol and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 60 publications
2
20
0
1
Order By: Relevance
“…Interestingly, five Suc-binding proteins showed opposite expression trends, their relative abundance decreased during seed filling (spots 405, 463, 522, 631, and 754). The expression profiles of these proteins may support previous investigations on the importance of Suc as a signaling molecule in seed and embryo development (Konradova et al, 2002;Bate et al, 2004;Yang et al, 2004; for review, see Borisjuk et al, 2004).…”
Section: Multiple Isoforms For Suc-binding Protein and Suc Synthase Ssupporting
confidence: 81%
“…Interestingly, five Suc-binding proteins showed opposite expression trends, their relative abundance decreased during seed filling (spots 405, 463, 522, 631, and 754). The expression profiles of these proteins may support previous investigations on the importance of Suc as a signaling molecule in seed and embryo development (Konradova et al, 2002;Bate et al, 2004;Yang et al, 2004; for review, see Borisjuk et al, 2004).…”
Section: Multiple Isoforms For Suc-binding Protein and Suc Synthase Ssupporting
confidence: 81%
“…The increase in SPS enzyme activity under stress was however not associated with sucrose content. Although sucrose synthase was favourable towards sucrose synthesis under stress, activity levels compared to SPS indicated that sucrose synthesis was solely dependent on the activity of SPS as previously reported in wheat stems at anthesis by Yang et al, (2004), and that this enzyme does not play a decisive role in regulating sucrose levels in sweet sorghum stems. Of the key sucrose metabolizing proteins investigated, invertases were significantly up-regulated by stress in both varieties, thus attributing to the observed hexose accumulation under stress.…”
Section: Discussionsupporting
confidence: 63%
“…In Arabidopsis, the sugar induction effect on anthocyanin accumulation is established via a sucrose specific pathway (Teng et al 2005;Solfanelli et al 2006), and the disaccharide analogs palatinose and turanose were used to illustrate the sucrose-specific signaling pathway in potato tubers and barley embryos (Yang et al 2004). But in our model, the sucrose-specific mechanism did not seem to be involved.…”
Section: Discussionmentioning
confidence: 96%